1975
DOI: 10.1021/jo00891a016
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical study of the mechanism of the conversion of phenyl(trichloromethyl)carbinol to .alpha.-methoxyphenylacetic acid

Abstract: chloronortricyclene (13x) (31%) and exo.endo-3-methoxy-5-chloronortricyclene (13,n) (18%), respectively, by nmr comparison with authentic samples.16 A third nonester product was assigned the structure exo.endo-3,5-dimethoxynortricyclene (14) (5%): nmr (CDCls) 3.97 ('os, 1), 3.52 (t, 1), 3.30 (s, 6), and 2.2-1.2 ppm (6); mass spectrum (70 eV) m/e 154 (M+). The major ester product was indentified as exo,exo-3-methoxy-5-carbomethoxynortricyclene (11) (34%) by vpc and nmr comparison with an authentic sample.7 The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Racemization occurs about eight times faster than the substitution of the chlorine by hydroxyl. Racemization involves the formation of an enolate anion whereas substitution proceeds unimolecularly via an a-lactone (3,8). The relatively easy racemization of the a-chloroacetate anion makes it difficult to tell how much racemization occurs during the intramolecular migration of the chlorine.…”
Section: Stereochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Racemization occurs about eight times faster than the substitution of the chlorine by hydroxyl. Racemization involves the formation of an enolate anion whereas substitution proceeds unimolecularly via an a-lactone (3,8). The relatively easy racemization of the a-chloroacetate anion makes it difficult to tell how much racemization occurs during the intramolecular migration of the chlorine.…”
Section: Stereochemistrymentioning
confidence: 99%
“…Accordingly, the observed results are consistent with complete racemization during the intramolecular chlorine migration to form chloro acetate, with the observed 9% of inverted chloro acid arising from the 17% of product not formed by the intramolecular pathway. It has previously been shown that the optical activity of the starting phenyl(trichloromethyl)carbinol is unchanged by treatment with methanolic potassium hydroxide at 40°C for 90 min (3).…”
Section: Stereochemistrymentioning
confidence: 99%
“…Phenyl(trichloromethyl)carbinol is known to react with methanolic potassium hydroxide at 50°C by pathway one to form a-methoxyphenylacetic acid in 70 to 80% yield (10); and dimethyl(trichloromethyl)carbino1 (chloretone) is known to react with sodium ethoxide in ethanol to form ethyl a-ethoxyisobutyrate in 72% yield (ll), and with …”
Section: Reaction With Methanolic Potassium Hydroxidementioning
confidence: 99%
“…Most of the various reactions summarized above can occur by either of two possible mechanisms (10). In both of the mechanisms the (trichloro-'Taken in part from the doctoral thesis of Thomas F. Steckel, University of Maryland, 1970. methy1)carbinol is first converted in situ into epoxide 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation